GAMBARAN PENGETAHUAN REMAJA TENTANG PERILAKU SEKSUAL PRANIKAH DI SEKOLAH MENENGAH ATAS - Stevenanderson steven (Yayasan Pendidikan Medika Indonesia, 2021)
Description of Adolescent Knowledge About Premarital Sexual Behavior in High School ABSTRACT Premarital sexual behavior is the biggest problem of various cases of juvenile delinquency. Cases from year to year show an increase in the incidence of premarital sex among teenagers. Low knowledge about sexuality needs to be anticipated because it will have an impact on the future of adolescents. This research was conducted with the aim to find out the description of adolescent knowledge about premarital sexual behavior in the high school in Pekanbaru city. The research was quantitative descriptive with a sample size of 119. Data were collected using a questionnaire and analyzed univariately. This study only describes respondents' knowledge about premarital sex. The results of this study are based on knowledge about premarital sex in high school in Pekanbaru city found 73 people (61.3%) who have good knowledge about premarital sex, quite as many as 39 people (32.8%), who have poor knowledge about premarital sex as many as 7 people (5.9%). The level of knowledge of students about premarital sex majority of the level of good knowledge, the advice given should be the school to do health promotion about the dangers of free sex to students in order to further increase knowledge and for parents to make observations of sexual behavior in adolescents. References : 40 (2009 - 2017) Keywords : Knowledge, Teenagers, Premarital sex